EDUCATIONAL DEMOCRACY IN THE PERSPECTIVE OF ISLAMIC EDUCATIONAL PHILOSOPHY - Diki Arwinsyah; Salminawati Salminawati; Usiono Usiono (TA'DIB: JURNAL PENDIDIKAN ISLAM, 2022)
Democracy has a set of values that are characteristic for achieving the goals of democracy itself. The development of democracy is still experiencing changes for the better. It can be seen that the discussion of democracy has expanded not only in the political and economic fields, but has also developed in the field of education. Educational democracy means that there is freedom given to educational actors in order to increase progress in the world of education. Islam has advised its people to treat others as they treat themselves. Islam also calls for the principle of equality and equal opportunities in learning, so that an awareness of learning is opened for everyone, without any differences between the rich and the poor and the socio-economic status of a student